Baby Blessings : A Prayer for the Day You Are Born - Jordan, Deloris; Ransome, James (New York : Simon & Schuster Books for Young Readers, 2010)
"This celebration of family life exalts the blessings and hopes a mother and father feel for their new baby. The text consists of the baby's parents' simple declarations of reassurance, love, and inspiration."--Amazon.com.
Keywords: Children -- Prayers and devotions; Children -- Prayers and devotions